Shared Experiences of Resilience Amongst Couples Where One Partner Is Living With Dementia—A Grounded Theory Study - Conway, Lucy; Wolverson, Emma; Clarke, Chris (Frontiers in Medicine, 2020)
Resilience is a concept which may help explain how older people are able to live well with dementia. Existing resilience research in dementia focuses on the caregiver and relatively little is known about how dyads (person with dementia and care partner) experience resilience. Using constructivist grounded theory, this qualitative study aimed to develop a theory of shared resilience amongst couples where one partner is living with dementia. Interviews were conducted with 12 dyads (n=24) to explore their shared understanding of resilience, what helps to develop and maintain their resilience and how resilience shapes their relationship and mutual well-being. Findings indicate that resilience was experienced as continuing with a ‘normal’ life as a couple notwithstanding the impact of dementia. This is in contrast to models of resilience which emphasize bouncing back or flourishing in the face of adversity. Instead couples described a shared resilience that enabled them to maintain their couplehood, a sense of togetherness and reciprocity in their relationship which in turn provided a further source of resilience. Findings emphasize the importance of dyadic research in developing a clearer understanding of the experience of living well with dementia. Interventions aimed at building resilience should engage dyads to consider how the couple’s shared resilience can be maintained and enhanced.